Global Approach in Safety Testing ICH Guidelines Explained - van der Laan, Jan Willem.; DeGeorge, Joseph J. (AAPS Advances in the Pharmaceutical Sciences Series, 2013)
The International Conference on Harmonisation of Technical Requirements for Registration of Pharmaceuticals for Human Use (ICH) is a unique project that brings together the regulatory authorities of Europe, Japan and the US and experts from the pharmaceutical industry in the three regions to discuss scientific and technical aspects of product registration. In Japan, the members are the Ministry of Health, Labour and Welfare (MHLW), and the Japan Pharmaceutical Manufacturers Association (JPMA). In Europe, the members are the EU (Representatives of the European Commission and the European Medicines Agency [EMA]), and the European Federation of Pharmaceutical Industries and Associations (EFPIA). In the United States, the members are the Food and Drug Administration (FDA), and the Pharmaceutical Research and Manufacturers of America (PhRMA). The International Federation of Pharmaceutical Manufacturers Associations (IFPMA) is the secretariat of the ICH. Additional members include Observers from WHO, European Free Trade Association (EFTA), and Canada. The Observers represent non-ICH countries and regions. This volume considers one of ICHs major categories, Safety, covering topics relating to in vitro and in vivo pre-clinical studies (Carcinogenicity Testing, Genotoxicity Testing, etc.). Since the start of the ICH process, many guidelines have been written, but in most cases there is a lack of awareness of the many issues that were addressed during the development of the consensus guidances.Further, just as it is important to understand what the guidances state, it is also important to understand the thoughts, debates, and intent of the experts involved, which are not included in the guidance documents. Why has the guideline been written as it is written, why are some topics ignored, and why have some initial guidance proposals have been deleted. These and other related questions and answers are the contents of this book, written by experts who were directly involved in writing the ICH guidances that drive drug development today.